2012
DOI: 10.1107/s0108270112044393
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[nickel(II)-μ2-[1,3-bis(imidazol-1-ylmethyl)benzene-κ2N3:N3′]-μ2-(5-carboxybenzene-1,3-dicarboxylato-κ4O1,O1′:O3,O3′)] 0.41-hydrate]

Abstract: The title compound, {[Ni(C(9)H(4)O(6))(C(14)H(14)N(4))]·0.41H(2)O}(n), exhibits a three-dimensional hydrogen-bonded supramolecular framework. The Ni(II) cation is six-coordinated in a distorted triangular prism defined by two N atoms from two 1,3-bis(imidazol-l-ylmethyl)benzene (bix) ligands and four O atoms from two 5-carboxybenzene-1,3-dicarboxylate (HBTC) dianions. The bix molecules and HBTC dianions both act as bidentate ligands, linking the Ni(II) cations to form a one-dimensional coordination polymer. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Interestingly, the coordination geometry of Cd(II) corresponds to a slightly distorted triangular prism (Figure b), with four oxygen atoms (O1, O1A, O2, O2A; A = 1 – x , y , 1/2 – z ) comprising the equatorial plane, while the other two oxygen atoms (O6, O6A) from two coordinated water molecules locate at the same side of the plane instead of the usual axial positions. Although recently Alvarez reported that the number of trigonal prisms throughout the six-coordinated transition-metal centers is barely 1.0% in the Cambridge Structural Database (CSD), this geometry is significant for it is observed in the active sites of molybdenum- and tungsten-containing enzymes and may appear as an intermediate or a transition state in the intramolecular racemization reactions. , For coordination polymers, as far as we known, the frequency of Mn(II) trigonal-prismatic structures is slightly high, but such coordination geometry has not been in Cd(II) polymers to date. , This example may make the coordination chemistry of Cd(II) complexes more substantial.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the coordination geometry of Cd(II) corresponds to a slightly distorted triangular prism (Figure b), with four oxygen atoms (O1, O1A, O2, O2A; A = 1 – x , y , 1/2 – z ) comprising the equatorial plane, while the other two oxygen atoms (O6, O6A) from two coordinated water molecules locate at the same side of the plane instead of the usual axial positions. Although recently Alvarez reported that the number of trigonal prisms throughout the six-coordinated transition-metal centers is barely 1.0% in the Cambridge Structural Database (CSD), this geometry is significant for it is observed in the active sites of molybdenum- and tungsten-containing enzymes and may appear as an intermediate or a transition state in the intramolecular racemization reactions. , For coordination polymers, as far as we known, the frequency of Mn(II) trigonal-prismatic structures is slightly high, but such coordination geometry has not been in Cd(II) polymers to date. , This example may make the coordination chemistry of Cd(II) complexes more substantial.…”
Section: Resultsmentioning
confidence: 95%
“…19,20 For coordination polymers, as far as we known, the frequency of Mn(II) trigonalprismatic structures is slightly high, but such coordination geometry has not been in Cd(II) polymers to date. 21,22 This example may make the coordination chemistry of Cd(II) complexes more substantial. The Cd−O bonds distances vary from 2.262(3) to 2.368(3) Å, and the O−Cd−O angles are in the range from 55.63°to 141.33°, which are similar to previously reported works.…”
Section: ■ Results and Discussionmentioning
confidence: 99%